Clinico-epidemiological profile and predictors of outcome in children with diphtheria: a study from northern India. (April 2019) - Dash, Nabaneeta; Verma, Sanjay; Jayashree, Muralidharan; Kumar, Rakesh; Vaidya, Pankaj C; Singh, Meenu
Diphtheria, a vaccine preventable disease in children, is still being reported from India. Details of 99 children with a clinical diagnosis of diphtheria admitted to a paediatric tertiary care teaching and referral hospital between January 2008 and December 2015 were collected retrospectively and analysed. The median (interquartile range [IQR]) age of the study group was 7.0 years (IQR = 5.0–8.0 years). Nearly two-thirds were unimmunised. Clinical features included fever (97%), dysphagia (82%), sore throat (67%), bull neck (54%), stridor (40%), neuropathy (27%) and nasal discharge (14%). Throat swab for Albert stain was positive in only 21% of cases and C. diphtheriae was isolated in only 28%. Complications included airway compromise (61.7%) followed by myocarditis (35.4%), acute kidney injury (22.3%), thrombocytopenia (25.3%) and neuropathy (27.3%). In all, 66% survived, 23% died and 11% opted for discontinuity of care owing to unfavourable prognoses. On multivariable logistic regression analysis, shorter duration of symptoms before presentation to our hospital was an independent predictor of unfavourable outcome (adjusted odds ratio = 0.88, 95% confidence interval = 0.79–0.99, P = 0.03).